2006
DOI: 10.1002/jmv.20646
|View full text |Cite
|
Sign up to set email alerts
|

High-risk HPV types in Tunisia. A pilot study reveals an unexpectedly high prevalence of types 58 and 82 and lack of HPV 18 among female prostitutes

Abstract: "High-risk" HPVs (HR-HPV) have sharply different prevalences and there is evidence to suggest this may vary according to regions. Accurate description of HR-HPV circulation is a key feature for the rational design of prevention and screening campaigns. To gain insight into HR-HPV circulation in Tunisia, a pilot study was carried out on 64 healthy prostitutes working in the Tunis area. HPV detection and typing were carried out by MY09/MY11 PCR and restriction fragment length polymorphism (RFLP). A selected set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
3
13
0
3
Order By: Relevance
“…The prevalence of cervical HPV infection found in our study is similar to previous reports in our country. Cervical HPV was thus found in 39.2% of prostitutes from Sousse and in 43.7% of those from Tunis 28 29. The carriage of high oncogenic risk HPV types was also reported in these studies.…”
Section: Discussionsupporting
confidence: 63%
“…The prevalence of cervical HPV infection found in our study is similar to previous reports in our country. Cervical HPV was thus found in 39.2% of prostitutes from Sousse and in 43.7% of those from Tunis 28 29. The carriage of high oncogenic risk HPV types was also reported in these studies.…”
Section: Discussionsupporting
confidence: 63%
“…We only have information about alcohol use in studies done in the Eastern Mediterranean region where one study reported all FSW were habitual alcohol users [26], and others reported that 50% currently drank [19]. …”
Section: Resultsmentioning
confidence: 99%
“…This finding may be explained by geographical prevalence of this genotype in some Mediterranean countries [22,23] and immigration from South America where this genotype is the second most frequently detected after HPV16 [24] . It is worth mentioning that according to the PATRICIA preliminary results [10] , vaccination against HPV16 and 18 is not effective against HPV58, whereas a cross-protection effect is seen for genotypes 31, 33 and 52.…”
Section: Discussionmentioning
confidence: 98%